Phosphorus dissolution pattern of different rock phosphates and its influence on biomass production and nodulation of Pueraria Phasoloides - Varghese A; Karthikakuttyamma M; Mathew M (Indian Journal of Natural Rubber Research, 1991)
Dissolution of four indigenous rock phosphates in comparison with an imported (Jordan) material was studied in an acid soil from rubber growing tract under field capacity for a period of ten weeks. Significant increase in Bray Extractable P was obtained for all the treatments. Dissolution of imported (Jordan) rock phosphate was the highest followed by that of Mussoorie rock phosphate. Rock phosphates from different geographical regions differed in their effect on dyr matter yield and P uptake of Pueraria phaseoloides. Among the Indian sources, Mussoorie rock phosphate was the most effective for Pueraria phaseoloides and it was on par with imported rock phosphate. The relative agronomic effectiveness of the different sources of rock phosphates followed the order - Jordan, Mussoorie, partially acidulated Maton, Purulia, Udaipur, Maton.
Keywords: Indigenous rock phosphate; Indigenous rock phosphate; Phosphorus dissolution pattern; Phosphorus dissolution pattern; Pueraria Phaseoloides; Pueraria Phaseoloides